2020
DOI: 10.1075/ihll.23.02gee
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism, second language acquisition, and language contact

Abstract: This chapter introduces the central issues and concepts in the fields of bilingualism, contact linguistics, and second language acquisition, with an eye to identifying generalizations and key distinctions. For example, although authors use terms like transfer, interference, bilinguals, etc., across fields, these sometimes have the same meaning and other times depend on the subfield of linguistics in which they are employed. While there is a good deal of overlap between these fields, the current chapter provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Specifically, we expect that time of action will demonstrate change across levels, given previous research on study abroad and university Spanish learners that has shown learners to overselect or overallow the PP in temporally remote contexts at earlier levels or with less language experience compared to later levels (Zahler & Whatley 2023;McAlister 2019). However, we do not anticipate significant change in the other constraints analyzed in the current study: verb lexical aspect, sequencing, and presence of temporal adverb, given that these constraints show variable findings in previous research both abroad and in the university context (e.g., Zahler & Whatley 2023;Geeslin et al 2012;Geeslin et al 2015;Linford 2016;McAlister 2019;Terán 2020;Whatley 2013). Specifically, in Zahler and Whatley (2023), these constraints generally demonstrated the same direction of effect for learners, but only varied in whether they were significant.…”
Section: Comparison Across Statistical Models In Second Language Studiescontrasting
confidence: 66%
See 3 more Smart Citations
“…Specifically, we expect that time of action will demonstrate change across levels, given previous research on study abroad and university Spanish learners that has shown learners to overselect or overallow the PP in temporally remote contexts at earlier levels or with less language experience compared to later levels (Zahler & Whatley 2023;McAlister 2019). However, we do not anticipate significant change in the other constraints analyzed in the current study: verb lexical aspect, sequencing, and presence of temporal adverb, given that these constraints show variable findings in previous research both abroad and in the university context (e.g., Zahler & Whatley 2023;Geeslin et al 2012;Geeslin et al 2015;Linford 2016;McAlister 2019;Terán 2020;Whatley 2013). Specifically, in Zahler and Whatley (2023), these constraints generally demonstrated the same direction of effect for learners, but only varied in whether they were significant.…”
Section: Comparison Across Statistical Models In Second Language Studiescontrasting
confidence: 66%
“…However, they do coincide with previous research on preterit and PP variation that indicates that L2 Spanish learners overuse or overselect the PP form in typically preterit contexts, that is, those that are temporally bound in the past and separate from the present (e.g., yesterday, a week ago, a year ago). This overuse and selection of the PP in preterit contexts occurs in several previous studies on study abroad, which provide a snapshot of development, as well as in at-home research, some of which is crosssectional as a proxy for development (Zahler & Whatley 2023;Geeslin et al 2012;Kanwit et al 2015;McAlister 2019;Terán 2020). In the U.S. university context specifically, only McAlister (2019) and Terán (2020) have examined preterit and PP form variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations